On the use of FLAKE in SURFEX coupled to Meso-NH - Salgado, Rui (2017)
Motivation: - Return to FLake, almost 10 years after the coupling with SURFEX - Availability of a set of data: exploitation of ALEX 2014: A field experience conducted around the Alqueva reservoir - A new running field campaign ALOP - Return to the question of the impact of ALqueva on local climate: 15 years after the close of the gates (Salgado, 2016, Policarpo et al., 2017) - Collaboration with the IPMA (Portuguese met office) in improving the local AROME physiography and activate FLake: improve weather forecast for the region - Use FLake in studies about surface carbon fluxes and algal blooms - Test the possibility of using FLake approach and results to forecast: water temperature, Evaporation from the reservoir, water quality parameters